1996
DOI: 10.1085/jgp.107.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea binding to a low-affinity site inhibits the Na/K-ATPase and the KATP channel in insulin-secreting cells.

Abstract: A B ST RA C T We have used hamster insulinoma tumor (HIT) cells, an insulin-secreting tumor cell line, to investigate modulation of the Na/K-ATPase and of the ATP-sensitive K channel (KATe) by the sulfonylurea glyburide. Membrane proteins from cells cultured in RPMI with 11 mM glucose have at least two glyburide receptor populations, as evidenced by high and low binding affinity constants, (Kd = 0.96 and 91 nM, respectively). In these cells KATP channel activity was blocked by low glyburide concentrations, IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Evidently, such balance also exists in the amphiphilic structure of glyburide, allowing its interaction with the postulated amphiphilic binding site on the enzyme [9]. Mechanistic issues aside, our present data indicate that depending on the prevailing ATP concentrations, Na + /K + -ATPase may indeed be either activated or inhibited by glyburide concentrations, up to 500 lM, that are often used for the presumed specific inhibition of the plasma membrane K ATP channels in various cell types [10,29]. This, and the possibility that plasma membrane K ATP channels of different cells may have different sulfonylurea sensitivities [23], suggest the necessity of caution in the use of glyburide in studies where the proposed interaction between Na + /K + -ATPase and any K ATP channel is examined.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Evidently, such balance also exists in the amphiphilic structure of glyburide, allowing its interaction with the postulated amphiphilic binding site on the enzyme [9]. Mechanistic issues aside, our present data indicate that depending on the prevailing ATP concentrations, Na + /K + -ATPase may indeed be either activated or inhibited by glyburide concentrations, up to 500 lM, that are often used for the presumed specific inhibition of the plasma membrane K ATP channels in various cell types [10,29]. This, and the possibility that plasma membrane K ATP channels of different cells may have different sulfonylurea sensitivities [23], suggest the necessity of caution in the use of glyburide in studies where the proposed interaction between Na + /K + -ATPase and any K ATP channel is examined.…”
Section: Discussionmentioning
confidence: 55%
“…Since this drug has been used in a number of studies to explore the mechanism of suggested functional interaction between Na + /K + -ATPase and the plasma membrane K ATP channels of renal epithelia and other cell types [29], the possibility of its direct interaction with Na + /K + -ATPase has been considered before [10][11][12]. However, when glyburide effects on Na + /K + -ATPase activities of crude isolated membranes or homogenates have been attempted, either inhibition [10] or lack of effect [11] have been reported. The present data on the purified kidney enzyme clearly show both activating and inhibitory effects of Membranes were prepared and assays were done at 5 mM ATP as indicated in Materials and methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glibenclamide, as an intervention agent, also works in other sites, antagonizing thromboxane A2 receptors and inhibiting Na+/K+ ATPase. [29] The understanding of the interactive nature of tissue protection mechanisms (cellular, inflammatory, endothelial, tubular, etc.) is still imprecise and of difficult distinction.…”
Section: Discussionmentioning
confidence: 99%